NAGIOS UNTUK MONITORING SERVER DENGAN PENGIRIMAN NOTIFIKASI GANGGUAN SERVER MENGGUNAKAN EMAIL DAN SMS GATEWAY (STUDI KASUS : PT. GAMATECHNO INDONESIA â YOGYAKARTA) - Asri, Nurul Fatmawati; Hamzah, Amir; Sholeh, Mohammad (Jurnal Jarkom, 2014)
ABSTRACTThe research is dedicated to built a monitoring system server using nagios with alert notification delivery when the server sustain an alert by email and sms. notification server status delivery is submitted to network administrator to easier admins work in order to monitoring server without being at the office. monitoring server is applied on to 3 host servers in PT Gamatechno Indonesia, which is localhost host monitoring server,âgtserverâ host and âgtgforgeâ host. The sending of notification message about system failure on the server can be done by setting the configuration file in the nagios monitoring system. Notification message server status delivery by email in this research is done with postfix mail transfer agent. Notification server status delivery by sms using gammu daemon and wavecome Fastrack M1306B as an sms gateway modem. mysql database, generated with gammu, is used as a storage media for sms data from nagios status delivery. PhpMyAdmin role as database management. As a final result, it shows the notification messages server status delivery using email and sms is accepted by admin succesfully. notification messages server status delivery has been sent are saved in gammu database.Keywords: Network Monitoring, Notification, Gammu, Nagios, Email, SMS Gateway